Literacy and the law in Lombard government. - Everett, Nick (Early Medieval Europe, 2000)
This article examines the Lombard law code as evidence for literate practices in government and society in seventh- and eighth-century Italy. The effectiveness of the code as an instrument of government is testified by the charter evidence, in which the precepts of the code are implicitly acknowledged or cited directly. Although largely the result of a necessary appropriation of late Roman property law, Lombard legislation and notarial practice applied further literate methods to document, and hence to validate, a range of transactions. The use of written law was not merely limited to male landowners, but affected Italo-Lombard society more widely, as is revealed by the evidence for women's property rights and manumission. The charter evidence and references within the code itself suggest that various uses of writing for governmental administration extended beyond the royal and ducal levels into local society.